2007
DOI: 10.1007/s00125-007-0624-1
|View full text |Cite
|
Sign up to set email alerts
|

Are glomerular volume differences between type 1 and type 2 diabetic patients pathologically significant?

Abstract: The observation that patients with type 2 diabetes tend to have larger glomeruli than patients with type 1 diabetes was first made more than 10 years ago. It has also been noted that type 2 diabetic patients with nephropathy often have more heterogeneous renal function and structure than type 1 patients. However, whether these observations are linked or have any bearing on the progression of nephropathy in the two types of diabetes remains uncertain. Here we put forward several hypotheses as to why glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
11
0
2
Order By: Relevance
“…On the other hand, patients with Type 2 diabetes are generally over the age of 40 and have evidence of age-related glomerulosclerosis, together with other propagators of renal disease, such as hypertension, obesity and dyslipidaemia. Thus nephropathy in Type 2 diabetes reflects a heterogeneous combination of kidney diseases precipitated by a mixture of mechanisms that may modify and overwhelm the typical renal responses to hyperglycaemia and the features of pure diabetic nephropathy [71]. Consequently, it has been suggested that, in terms of responses to treatment, Type 1 and Type 2 diabetic patients should be considered separately.…”
Section: C-peptide In Type 2 Diabetesmentioning
confidence: 98%
“…On the other hand, patients with Type 2 diabetes are generally over the age of 40 and have evidence of age-related glomerulosclerosis, together with other propagators of renal disease, such as hypertension, obesity and dyslipidaemia. Thus nephropathy in Type 2 diabetes reflects a heterogeneous combination of kidney diseases precipitated by a mixture of mechanisms that may modify and overwhelm the typical renal responses to hyperglycaemia and the features of pure diabetic nephropathy [71]. Consequently, it has been suggested that, in terms of responses to treatment, Type 1 and Type 2 diabetic patients should be considered separately.…”
Section: C-peptide In Type 2 Diabetesmentioning
confidence: 98%
“…Also, in the majority of individuals with type 1 diabetes, chronic hyperglycemia and its consequences are the only evident causes of nephropathy, whereas in type 2 diabetes nephropathy more typically reflects a combination of heterogeneous renal insults caused by a mixture of mechanisms that may alter and overcome renal responses to hyperglycemia and the features of pure diabetic nephropathy (36,51). Consequently, commentators suggest that in terms of responses to treatment, type 1 and type 2 diabetic subjects should be considered independently (36,51). More study of C-peptide (patho)physiology in type 2 diabetes is required to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Mesangial matrix formation rather than proliferation of mesangial cells corresponds most closely with declining GFR (Steffes et al, 1992). Growth of the mesangial matrix component of the mesangium is the main contributor to glomerular enlargement in Type 1 diabetic patients (White et al, 2007). The enlarged diabetic glomerulus shown in Figure 3 contains increased mesangium and fewer open capillaries than normal.…”
Section: Glucose Induced Toxicity To the Kidneymentioning
confidence: 99%